1965
DOI: 10.1084/jem.122.4.651
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Skin Homograft Rejection on Recipient and Donor Mixed Leukocyte Cultures

Abstract: The discovery of the mitogenic (1) and lymphocyte transforming (2) properties of phytohemagglutinin (PHA) was soon followed by the finding that many antigens (3, 4) and vaccines (5) were also able to stimulate peripheral lymphocytes to proliferate in short-term cultures, provided the cell donor had been previously sensitized with the antigen. Histocompatibility antigens also produce lymphocyte transformation and mitoses without preceding sensitization in mixed leukocyte cultures of unrelated individuals (6). A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

1967
1967
1989
1989

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…O ppenheim et al (10) observed an enhanced response to PHA in vitro of lymphocytes from patients with ataxia telangiectasia during homograft rejection. Similar results were obtained with lympho cytes from normal individuals during homograft rejection (34,35).…”
Section: Discussionsupporting
confidence: 76%
“…O ppenheim et al (10) observed an enhanced response to PHA in vitro of lymphocytes from patients with ataxia telangiectasia during homograft rejection. Similar results were obtained with lympho cytes from normal individuals during homograft rejection (34,35).…”
Section: Discussionsupporting
confidence: 76%
“…The findings that the MLR was negative in cultures of lymphocytes from monozygotic twins [2,11] and that the incidence of negative reactions in cultures of leucocytes from siblings was greater than in cultures from un related subjects [1,3,4,5] suggests that the reaction has a genetic basis. The increased 'strength' of reaction in cultures made after skin grafting the subjects [3,14] supports the view that histo compatibility antigens may determine the degree of lymphocyte transformation, and it was suggested that only the strongest histo compatibility locus was important in determining the degree of reaction [11]. Studies of the MLR in inbred rat strains have indicated…”
mentioning
confidence: 63%
“…It was proposed to explore the mixed lymphocyte culture reaction (MLR) as a potential histo compatibility test in vitro [3,1]. This view was supported by the finding that the number of transformed cells in MLR of skin graft donors and recipients increased at the time of graft rejection [11].…”
mentioning
confidence: 73%